Discovery of novel indirubin-3′-monoxime derivatives as potent inhibitors against CDK2 and CDK9. Issue 11 (1st June 2015) - Yan, Lei; Lai, Fangfang; Chen, Xiaoguang; Xiao, Zhiyan
Graphical abstract: Abstract: Indirubin-3′-monoxime (IM) is a potent cyclin-dependent kinase (CDK) inhibitor. Twenty novel IM derivatives were prepared to investigate the structure–activity relationships (SAR) of this compound class. Six compounds showed significant inhibition against both CDK2/cyclin E1 and CDK9/cyclin T1. The most potent compound7t exhibited IC50 values at submicromolar level. Preliminary SAR trends were suggested and cytotoxicity of these compounds was investigated. Molecular docking studies on compounds7l and7t provided conducive clues for further structural optimization.